VARIABILITY ANALYSIS OF FACTORS AFFECTING NUTRITION AND MYCOTOXIN CONTAMINATION IN RAW CORN IN NORTH SUMATRA - Mahyuzar, Mahyuzar; Tafsin, Ma’ruf; Ginting, Simon P. (Buletin Veteriner Udayana, 2020)
The purpose of this study was to determine factors that influence nutritional variability and mycotoxin contamination in corn as raw materials in North Sumatra by observed the correlation between independent variables (corn varieties, planting land, elevation, relative humidity, source of drying, storage time, and storage area) with each dependent variables (the level of moisture, crude protein, crude fat, crude fiber, aflatoxin, fumonisin, and zearalenone). From 5 chosen districts in North Sumatra, we interviewed 45 corn farmers, 30 corn traders, and 30 corn collectors and we also tested 105 corn samples from them. Samples were tested for moisture level t, crude protein level, crude fat level, crude fiber level, aflatoxin, fumonisin, and zearalenone. Aflatoxin, fumonisin, and zearalenone level test used the LFIA ( Lateral Flow Immunochromatic Assay ) method. Statistic analyzed by correlation and regression by using SPSS version 21.0. The results showed that the elevation factor had a significant effect on moisture and crude fiber level and storage time had a significant effect on water content. But none of the crude protein and crude fat levels were affected by any independent variable. In mycotoxin contamination, relative humidity factor had a significant effect on aflatoxin and fumonisin level, storage time had a significant effect on the aflatoxin level but zearalenone was not affected by any independent variable.